Perancangan Aplikasi Informasi SMS untuk Alumni Unsoed Menggunakan UML (Unified Modeling Language) - Wijayanto, Bangun; Taryana, Acep (Dinamika Rekayasa, 2007)
Unified Modeling Language (UML) is a language which have come to the standard in industry to visualize, design and document the software system. Using UML we can make model for All software application type, where the application can also written in many language. SMS (Short Message Service) is the best choice to solve geographic problems in spreading information to the alumni Unsoed. The aim of this research is to compile notation of UML (Unified Modeling Language) in development of SMS Server for Alumni Unsoed. This research is conducted with software engineer method. The design result of software SMS alumni Unsoed present that UML (Unified Modeling Language) help in design and software programming